PENGEMBANGAN PLATFORM KNOWLEDGE MANAGEMENT DAN E-COMMERCE UNTUK PEMBERDAYAAN DESA: ( Studi Kasus Website ADIDES ) - Gogor Arif , Handiwibowo; Gita Widi , Bhawika; Edwin , Setiawan; Reni, Nadlifatin; Fadila , Isnaisi; Dominggo Bayu, Baskara; Perdana Suteja, Putra (COMVICE: Journal Of Community Service, 2024)
The Association of Village Integrator Lecturers (ADIDES) was formed in response to the strong desire of academics (lecturers) to increase village capacity in serving their communities. The development of a digital platform in the form of the ADIDES website (adides.or.id) aims to increase academic collaboration and village economic empowerment through knowledge management and e-commerce. The background to this activity is the limited access of villages to intellectual resources, most of which are owned by universities. This community Service activity was carried out intensively both online and offline in the first half of 2024. The fostered partners involved were ADIDES member-fostered villages in Surabaya and Sidoarjo. The results of the implementation of the activity showed that the ADIDES website succeeded in facilitating the storage and sharing of knowledge, strengthening academic collaboration, and supporting the marketing of village products through e-commerce features. The level of participation and user satisfaction showed the effectiveness of this platform in supporting community service activities. This shows that the ADIDES website is able to increase connectivity between the academic world and villages, although there are still challenges, such as limited internet access in some villages.